Smart torch light / Cliff T. Richard … [et al.] - T. Richard, Cliff; Mohamad Sabari, Mohamad Amin; Mazlan, Muhamad Fauzi; A Rahman, Muhammad Ariff; Mohd Hamdan, Mohd Hadzamee (2018)
After several years working in the hospital we noticed that during patient assessment we need a lot of separate equipment to assess patient. For example sphygmomanometer to check blood pressure, pulse oximeter for SPO2, ECG machine for heart rhythm and torchlight for GCS assessment. We try to combine all the equipments into one simple equipment. Hence, we innovate a Smart Torch Light.